Intraspecific variation in aerobic and anaerobic locomotion: gilthead sea bream (Sparus aurata) and Trinidadian guppy (Poecilia reticulata) do not exhibit a trade-off between maximum sustained swimming speed and minimum cost of transport - Svendsen, Jon C.; Tirsgaard, Bjørn; Cordero, Gerardo A.; Steffensen, John F. (Frontiers in Physiology, 2015)
Intraspecific variation and trade-off in aerobic and anaerobic traits remain poorly understood in aquatic locomotion. Using gilthead sea bream (Sparus aurata) and Trinidadian guppy (Poecilia reticulata), both axial swimmers, this study tested four hypotheses: 1) gait transition from steady to unsteady (i.e. burst-assisted) swimming is associated with anaerobic metabolism evidenced as excess post exercise oxygen consumption (EPOC); 2) variation in swimming performance (critical swimming speed; Ucrit) correlates with metabolic scope (MS) or anaerobic capacity (i.e. maximum EPOC); 3) there is a trade-off between maximum sustained swimming speed (Usus) and minimum cost of transport (COTmin); and 4) variation in Usus correlates positively with optimum swimming speed (Uopt; i.e. the speed that minimizes energy expenditure per unit of distance travelled). Data collection involved swimming respirometry and video analysis. Results showed that anaerobic swimming costs (i.e. EPOC) increase linearly with the number of bursts in S. aurata, with each burst corresponding to 0.53 mg O2 kg-1. Data are consistent with a previous study on striped surfperch (Embiotoca lateralis), a labriform swimmer, suggesting that the metabolic cost of burst swimming is similar across various types of locomotion. There was no correlation between Ucrit and MS or anaerobic capacity in S. aurata indicating that other factors, including morphological or biomechanical traits, influenced Ucrit. We found no evidence of a trade-off between Usus and COTmin. In fact, data revealed significant negative correlations between Usus and COTmin, suggesting that individuals with high Usus also exhibit low COTmin. Finally, there were positive correlations between Usus and Uopt. Our study demonstrates the energetic importance of anaerobic metabolism during unsteady swimming, and provides intraspecific evidence that superior maximum sustained swimming speed is associated with superior swimming economy and optimum speed.